Nanomaterials Risks and Benefits - Linkov, Igor; Steevens, Jeffery A. (NATO Science for Peace and Security Series C: Environmental Security, 2009)
Many potential questions regarding the risks associated with the development and use of wide-ranging technologies enabled through engineered nanomaterials. For example, with over 600 consumer products available globally, what information exists that describes their risk to human health and the environment? What en- neering or use controls can be deployed to minimize the potential environmental health and safety impacts of nanomaterials throughout the manufacturing and product lifecycles? How can the potential environmental and health benefits of nanotechnology be realized and maximized? The idea for this book was conceived at the NATO Advanced Research Workshop (ARW) on "Nanomaterials: Environmental Risks and Benefits and Emerging Consumer Products. " This meeting - held in Algarve, Portugal, in April 2008 - started with building a foundation to harmonize risks and benefits associated with nanomaterials to develop risk management approaches and policies. More than 70 experts, from 19 countries, in the fields of risk assessment, decision-analysis, and security discussed the current state-of-knowledge with regard to nanomaterial risk and benefits. The discussion focused on the adequacy of available risk assessment tools to guide nanomaterial applications in industry and risk governance. The workshop had five primary purposes: Describe the potential benefits of nanotechnology enabled commercial products. Identify and describe what is known about environmental and human health risks of nanomaterials and approaches to assess their safety. Assess the suitability of multicriteria decision analysis for reconciling the benefits and risks of nanotechnology.